Ionic liquid-assisted hydroalkoxylation of hexafluoropropene with 2,2,2-trifluoroethanol: A mechanistic consideration - Kang, Je Eun; Lee, Je Seung; Kim, Dong Sub; Lee, Sang Deuk; Lee, Hyunjoo; Kim, Hoon Sik; Cheong, Minserk (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2009)
CF3CHFCF2OCH2CF3 (1,1,2,3,3,3-hexafluoropropyl-2',2',2'-trifluoroethylether), one of the third generation CFC alternatives, was obtained in high yield and selectivity from the hydroalkoxylation reaction of hexafluoropropene with 2,2,2-trifluoroethanol conducted in the presence of a catalytic system consisting of a potassium salt and an ionic liquid, 1-butyl-3-methylimidazolium chloride ([BMIm]Cl). The formation of commonly observed olefinic side products in the hydroalkoxylation catalyzed by potassium salts was greatly reduced by the co-presence of [BMIm]Cl. Theoretical calculations and mechanistic studies suggested that potassium ion is largely responsible for the formation of olefinic side products. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: HYDROFLUOROETHERS; ETHERS